The impact of tree loss on carbon management in West Africa. Issue 6 (29th November 2021) - Buchanan, Graeme M.; Field, Rob H.; Bradbury, Richard B.; Luraschi, Beatriz; Vickery, Juliet A.
Abstract: This study quantifies the amount of carbon stored and sequestered by vegetation in west Africa, carbon loss due to tree cover loss, and the potential natural sequestration relative to projected carbon emissions in 2030. GIS analysis of published data on vegetation biomass, tree cover, sequestration by vegetation and soil carbon indicate that vegetation and soil held 38, 855 Mt of carbon in 2010, most of which was in above and below ground vegetation. The loss of 58, 353 km 2 (9%) of tree cover between 2010 and 2018 resulted in the loss of 672 Mt of 14, 923 Mt carbon in vegetation. Key Biodiversity Areas, (sites of conservation importance), covered 7.4% of land but in 2010 contained 16% of carbon stored in vegetation. Trees sequestered between 23.6 and 53.6 Mt of carbon in 2018 (17% of which was in Key Biodiversity Areas). Restoration of the tree cover lost in west Africa between 2010 and 2018 could sequester an additional 27.5 Mt of carbon per annum during the first 30 years of growth. Our estimates indicate a combination of conservation and restoration of tree cover could sequester the equivalent of c.30% of projected 2030 regional emissions, contributing significantly towards mitigating climate change.